The recency ratio assessed by story recall is associated with cerebrospinal fluid levels of neurodegeneration biomarkers. (February 2023) - Bruno, Davide; Jauregi Zinkunegi, Ainara; Kollmorgen, Gwendlyn; Suridjan, Ivonne; Wild, Norbert; Carlsson, Cynthia; Bendlin, Barbara; Okonkwo, Ozioma; Chin, Nathaniel; Hermann, Bruce P.; Asthana, Sanjay; Zetterberg, Henrik; et al.
Abstract: Recency refers to the information learned at the end of a study list or task. Recency forgetting, as tracked by the ratio between recency recall in immediate and delayed conditions, i.e., the recency ratio (Rr), has been applied to list-learning tasks, demonstrating its efficacy in predicting cognitive decline, conversion to mild cognitive impairment (MCI), and cerebrospinal fluid (CSF) biomarkers of neurodegeneration. However, little is known as to whether Rr can be effectively applied to story recall tasks. To address this question, data were extracted from the database of the Alzheimer's Disease Research Center at the University of Wisconsin – Madison. A total of 212 participants were included in the study. CSF biomarkers were amyloid-beta (Aβ) 40 and 42, phosphorylated (p) and total (t) tau, neurofilament light (NFL), neurogranin (Ng), and α-synuclein (a-syn). Story Recall was measured with the Logical Memory Test (LMT). We carried out Bayesian regression analyses with Rr, and other LMT scores as predictors; and CSF biomarkers (including the Aβ42/40 and p-tau/Aβ42 ratios) as outcomes. Results showed that models including Rr consistently provided best fits with the data, with few exceptions. These findings demonstrate the applicability of Rr to story recall and its sensitivity to CSF biomarkers of neurodegeneration, and encourage its inclusion when evaluating risk of neurodegeneration with story recall.